2013
DOI: 10.3109/08958378.2012.756086
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of wood smoke PM2.5exposure on macrophage functions

Abstract: Epidemiological studies have shown a correlation between chronic biomass smoke exposure and increased respiratory infection. Pulmonary macrophages are instrumental in both the innate and the adaptive immune responses to respiratory infection. In the present study, in vitro systems were utilized where alveolar macrophages (AM) and bone marrow-derived macrophages (BMdM) were exposed to concentrated wood smoke-derived particulate matter (WS-PM) and mice were exposed in vivo to either concentrated WS-PM or inhaled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 60 publications
(85 reference statements)
3
43
0
1
Order By: Relevance
“…In rats, the lung shows minor pulmonary inflammation and reduced interleukin-1β after 70 days of in-vivo HAP exposure 73. Similar findings of reduced release of interleukin-8 by ex-vivo alveolar macrophages at baseline, and after further challenge with wood smoke particles, have been seen in human beings exposed to HAP 72,74. Adequate cytokine and chemokine responses are important for neutrophil recruitment 75.…”
Section: Respiratory Infectionsmentioning
confidence: 61%
See 1 more Smart Citation
“…In rats, the lung shows minor pulmonary inflammation and reduced interleukin-1β after 70 days of in-vivo HAP exposure 73. Similar findings of reduced release of interleukin-8 by ex-vivo alveolar macrophages at baseline, and after further challenge with wood smoke particles, have been seen in human beings exposed to HAP 72,74. Adequate cytokine and chemokine responses are important for neutrophil recruitment 75.…”
Section: Respiratory Infectionsmentioning
confidence: 61%
“…The little evidence available for subacute and chronic HAP exposure (in vivo) suggests that compensatory changes limit inflammatory responses in mice, with lower interferon-γ response in T-cell co-culture 7 days after exposure to wood smoke 72. In rats, the lung shows minor pulmonary inflammation and reduced interleukin-1β after 70 days of in-vivo HAP exposure 73.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…AhR and JNK-AP-1 activation has also been reported in submerged cultures of lung cells exposed to other types of biomass smoke. Migliaccio et al showed that mouse monocytes treated with particulate matter from wood smoke had increased expression of an AhR-regulated gene, and Martey et al found that human lung fibroblasts exposed to tobacco smoke extract displayed AhR nuclear translocation (31, 53). Additionally, increased levels of phosphorylated JNK were observed in human bronchial epithelial cells treated with wood smoke extract (26).…”
Section: Discussionmentioning
confidence: 99%
“…In mice and rats, long-term inhalation of woodsmoke in concentrations relevant for ambient exposure induces mild inflammatory effects in the airways, systemic inflammation and decreased lung function [17,[108][109][110][111][112]. Woodsmoke PM has also been reported to exacerbate allergic inflammation and allergic sensitisation, and to decrease pulmonary macrophage function in terms of impaired infection resistance [17,109,[112][113][114], this was recently demonstrated to apply equally to particles from Malawian and Norwegian woodsmoke [115]. Overall, in vivo and in vitro experiments demonstrate that woodsmoke PM can induce inflammatory responses, cytotoxicity, genotoxicity, oxidative stress and immunosuppressive effects [17, 93-95, 104, 111, 116-122].…”
Section: Toxicity Of Woodsmoke Particlesmentioning
confidence: 99%